An introduction to spherical orbit spaces - Jill Mcgowan; Catherine Searle (International Journal of Mathematics and Mathematical Sciences)
Consider a compact, connected Lie group G acting isometrically on a sphere Sn of radius 1. Two-dimensional quotient spaces of the type Sn/G have been investigated extensively. This paper provides an elementary introduction, for nonspecialists, to this important field by way of several classical examples and supplies an explicit list of all the isotropy subgroups involved in these examples.